2023
DOI: 10.1093/pcp/pcad032
|View full text |Cite
|
Sign up to set email alerts
|

Hyponastic Leaves 1 Interacts with RNA Pol II to Ensure Proper Transcription of MicroRNA Genes

Abstract: HYL1 (DRB1) is a double-stranded RNA binding protein involved in miRNA processing in plants. It is a core component of the Microprocessor complex and enhances the efficiency and precision of miRNA processing by the DCL1 protein. In this work, we report a novel function of the HYL1 protein in the transcription of MIR genes. HYL1 colocalizes with RNA Polymerase II and affects its distribution along MIR genes. Moreover, proteomic experiments revealed that the HYL1 protein interacts with many transcription factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
1
3
0
Order By: Relevance
“…2, E to H ). These results resemble previous results showing that HYL1 interacts with TOPLESS (TPL) and TOPLESS-RELATED (TPR1 and TPR2), Lish-WD40 proteins with functions in chromatin remodeling ( Bielewicz et al 2023 ). This suggests that HYL1 is prone to interact with regulatory factors, likely at the chromatin level.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…2, E to H ). These results resemble previous results showing that HYL1 interacts with TOPLESS (TPL) and TOPLESS-RELATED (TPR1 and TPR2), Lish-WD40 proteins with functions in chromatin remodeling ( Bielewicz et al 2023 ). This suggests that HYL1 is prone to interact with regulatory factors, likely at the chromatin level.…”
Section: Resultssupporting
confidence: 91%
“…Later, further research using HYL1 loss of function mutants revealed many biological aspects of this protein, positioning it as one of the major miRNA biogenesis components in plants. Recently, a few studies also hint at the possibility that HYL1 acts outside the miRNA biogenesis regulating miRNA-mediated translation inhibition and MIRNA transcription ( Yang et al 2021 ; Bielewicz et al 2023 ). Interaction assays revealed that HYL1 associates with TPL, TPR1, TPR2, and TPR4, which are Lish-WD40 proteins known to repress transcription ( Bielewicz et al 2023 ), indicating a tight link between the miRNA processing machinery and transcription.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations